Economics of native poultry rearing in the coastal regions of Bangladesh (Bangladesh Journal of Animal Science, 2013)
This study attempts to estimate the income from native poultry production and analyze the efficiency of resources used covering three coastal districts of Bangladesh namely Noakhali, Patuakhali and Satkhira. A total of 180 poultry rearers were selected from different villages of the districts using purposive sampling technique. Primary and secondary data were collected and analyzed following a combination of descriptive statistics, sensitivity analysis, statistical model and mathematical technique. Gross and net returns per household per day from native poultry rearing were estimated at Tk. 34.04 and Tk. 27.93, respectively. The undiscounted benefit cost ratio was 5.57, implying that this enterprise is highly profitable. Moreover, the contribution from poultry rearing to total income was 8.25 percent. Sensitivity analysis shows that the gross margins and benefit cost ratios were strongly influenced by the factors such as the cost of inputs, price of outputs and poultry inventory. Multiple Regression model revealed that almost all variables were influenced income from native poultry farming except rearing cost. Increasing returns to scale was found which indicates that there was bright prospect to earn more through the use of more inputs in the production process. Finally, a number of problems faced by the poultry farmers were identified and some suggestions were recommended accordingly. DOI: http://dx.doi.org/10.3329/bjas.v42i1.15781 Bang. J. Anim. Sci. 2013. 42 (1): 49-56